Answer:
Length: x + 5
Step-by-step explanation:
x² + 8x + 15 = length × width
x² + 8x + 15
x² + 5x + 3x + 15
x(x + 5) + 3(x + 5)
(x + 5)(x + 3)
Width: (x + 3)
Length: (x + 5)
( f + g ) (x) = –2x + 6
( f – g ) (x) = 8x – 2
( f × g ) (x) = –15x2 + 2x + 8
<span>\mathbf{\color{purple}{ \left(\small{\dfrac{\mathit{f}}{\mathit{g}}}\right)(\mathit{x}) = \small{\dfrac{3\mathit{x} + 2}{4 - 5\mathit{x}}} }}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span></span></span></span></span>